Aplikasi Pembelajaran Cara Merawat Hewan Peliharaan Untuk Anak Usia 4-6 Tahun Berbasis Augmented Reality - Siansi Arga Tantra; Emmy Wahyuningtyas; Beny Y.V Nasution (Informatics Engineering Department-UWKS, 2015)
At the level of kindergarten education today many things taught to introduce children to the outside world, one of which is the introduction of a pet. Teach and introduce about pets for children will improve their cognitive abilities. Research conducted Robert Poresky, sociologist from Kansas State University, USA, in 1988 concluded that the ability kognititf in children can be increased by having a pet. Having a pet is not just a psychological benefit, but also can have a positive impact on health. The positive impact on children is to eliminate stress, learn to be responsible and learn empathy. At this stage of child education kindergarten (4-6 years), students will tend to be more interested in learning medium in which there are animated images that attract attention. The more attractive a medium of learning, growing well in stimulating the cognitive ability of children to learn their way. Augmented Reality is a technology that is growing and attractive to serve as a medium of learning. Where it will be very helpful for kindergarten teachers or parents as learning media to introduce to children. To the authors create an interactive application as a medium of learning how to care for pets in children. Results of experiments conducted by using augmented reality visual media as a medium for introducing new learning in children how to care for pets, children are more interested in learning. It can be said that this application has been successfully lure children to learn with a high percentage rate of around 80.46%. The shortage of these applications, such as objects and animations are still not perfect.